Photodecomposition Profile of Organic Material during the Partial Solar Eclipse of 9 March 2016 and Its Correlation with Organic Material Concentration and Photocatalyst Amount - Asep Bayu Dani Nandiyanto; Desri Sofiani; Novie Permatasari; Tranmissia Noviska Sucahya; Ani Siti Wiryani; Annisa Purnamasari; Arvina Rusli; Eka Cahya Prima (Universitas Pendidikan Indonesia, 2016)
The present study investigated the photodecomposition of an organic material during the partial (88.76%) solar eclipse phenomenon of 9 March 2016 in Bandung, Indonesia. Curcumin and anatase titanium dioxide (TiO2) particles were used as models of organic material and photocatalyst, respectively. The influence of the process parameters (i.e., curcumin concentration and the amount of TiO2) on the photodecomposition process was also investigated. The results showed that the curcumin was decomposed along with the solar light irradiation time. During the solar eclipse, the photodecomposition rate is suddenly down. The partial solar eclipse provided a slower photodecomposition process than the process under sunny days (conducted on 8 and 10 March 2016). The concentration of curcumin and the amount of TiO2 also have played an important role in the photodecomposition, in which the lower concentration of curcumin and the higher amount of TiO2 have a correlation to the obtainment of higher photodecomposition rate.